Effectiveness of Behavioral Ivan Pavlov Conservation with Modeling Techniques to Increase Characters Helps Others Through Lesson Study - I Komang Ribek Budiarta Teja; I Ketut Dharsana; K Suranata (RedwhitePress)
This study aims to determine the effectiveness of behavioral counseling Ivan Pavlov with modeling techniques to improve the character of helping others through lesson study in first-grade students. This type of research is quasi-experimental with pre-test and post-test control group design. The sample was 36 students with df 35. The method of collecting data used a character questionnaire to help others as many as 30 items. The results of data analysis are the value of tcount 12,598 > ttable 2.03 so that Ho is rejected and Ha is accepted. So there are significant differences. It can be concluded that Ivan Pavlov's behavioral counseling is an effective modeling technique for improving character helping others.